PEMANFAATAN METODE CLUSTERING UNTUK MENGANALISIS PENDUDUK KEBUMEN YANG MEMILIKI KETERAMPILAN TEKNOLOGI INFORMASIDAN KOMUNIKASI (TIK) - Awaludin Abid; Rainaldi Putra Setiawan (Journal of Data Science Theory and Application, 2023)
Access to various forms of technology is considered important today in Indonesia, this is because if the government does not move quickly to make technology more user-friendly, the skills gap in information technology will continue to widen. The purpose of this study is to determine whether or not there are differences in the level of expertise or knowledge about information technology between communities, especially in Kebumen district. The clustering calculation uses survey data conducted by researchers given to friends, relatives and neighbors of researchers with data on the number of teenagers and adults aged 19-49 years. As one of the methods in unsupervised learning, the clustering algorithm is used so that the data set can be organized into groups with other items that are comparable to it. The results show that most of the age range who have IT expertise are more in the age range of 19-29 years.